Photoluminescent properties of TIO2 nanostructures prepared by hydrothermal method - Zamiri, Golnoush (2013)
The major problem facing in the fabrication of TiO2 nanostructure is about the control of its size and shape which have directly effect on its physical properties. The nanostructures prepared by hydrothermal method shows better structural,morphological and photocatalytic property. In the present study the fabrication of nanosize TiO2 prepared by hydrothermal technique using Ethylenediamine (EN) and Thiourea (TH) as solvent has been investigated. The objectives of the work is to present a systematic study on the growth and characterization of TiO2 nanostructures prepared by this method, and secondly, to experimentally study the effect of Mn doping on structural and photoluminescence properties of TiO2 nanostructures. In this hydrothermal method, TiO2 of micron size, EN and TH were dissolved in distilled water and then transferred to a teflon-lined autoclave. The precipitate was collected, washed with ethanol:water solution and then dried in an oven. The effect of temperature, time, precursors on structure and morphology of the TiO2 were studied. To see the effect of Mn on TiO2nanostructures, Mn, TiO2, EN and TH were dissolved in distilled water and then transferred to an autoclave. The obtained powders were characterized by FTIR and photoluminescence (PL) spectroscopies, XRD, EDX, SEM,and VSM. Characterization by SEM confirmed that the samples are well crystalline nanostructure. The XRD patterns of all the products have diffraction peaks which well agree with those of a standard anatase TiO2 (JCPDS No.21-1272). The SEM results show that the morphology of TiO2 using EN and TH changed when the sample prepared at various hydrothermal temperatures, times and precursors. The PL study shows that the band gap energy of the TiO2 nanomaterial increased to 3.23.eV compared to that of bulk state (3.20 eV). When doped with Mn, the XRD result confirmed that Mn goes into TiO2 crystal lattice and the crystallite size decreases. The SEM images show that the morphology of some pure TiO2 nanostructure was changed from nanorod and nanoparticle to flower-like after doping. The optical band-gap energy of the sample increases due to the decrease of material size and it behaved as a soft ferromagnet.